METHODOLOGICAL BASIS FOR ESTIMATING THE LIFE CYCLE COST OF AIRCRAFT ENGINE, TAKING INTO ACCOUNT THE ATTENDANT RISKS - E. A. Ozdoeva; O. A. Smolyakov (Вестник университета)
The formation and development of the main areas of technical and economic research in the field of aircraft engine building have been considered. A typical structure of the life cycle cost of an aircraft engine has been presented and typical tasks in the field of technical and economic efficiency, solved at different stages of the cycle, have been described. Also the method used to solve these problems at the stage of development work on the creation of the engine has been considered. The purpose of the study is to develop a risk assessment methodology for the creation of an aircraft engine, as well as its software implementation with subsequent integration into an existing design product. At this stage, it is necessary to describe clearly the algorithm that will be the basis for the risk assessment of the aircraft engine development.